2021
DOI: 10.3390/biomedicines9081020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Metformin in Relation to Diabetes Mellitus and Ovarian Cancer

Abstract: Since multiple reports established an association between diabetes mellitus and various cancers, emerging studies have surfaced to understand the effects of metformin as an anti-cancer agent. Although there was previous, but conflicting evidence, of a relationship between diabetes and ovarian cancer (OvCa), recent studies have supported this association. The mechanism of cancer development in patients with diabetes is likely to involve hyperglycemia, hyperinsulinemia, chronic inflammation, reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Over the years, phase I-III clinical trials of OC and metformin have been conducted. However, these trials are being conducted in Europe, the United States, and Australia, regions where the percentage of OCCC is low, and the target patients are "advanced stage OC," "serous carcinoma" and "endometrial carcinoma"; there are no clinical trials speci cally on OCCC [41]. Although our study used lower concentrations of metformin than previously reported, this is a limitation.…”
Section: Discussionmentioning
confidence: 94%
“…Over the years, phase I-III clinical trials of OC and metformin have been conducted. However, these trials are being conducted in Europe, the United States, and Australia, regions where the percentage of OCCC is low, and the target patients are "advanced stage OC," "serous carcinoma" and "endometrial carcinoma"; there are no clinical trials speci cally on OCCC [41]. Although our study used lower concentrations of metformin than previously reported, this is a limitation.…”
Section: Discussionmentioning
confidence: 94%
“…Diabetes-induced inflammation has been linked to the development of a variety of illnesses. As long-term hyperglycemia induces inflammatory response, vascular and target organs damage occurs ( Nolan et al, 2011 ), ultimately increasing the incidence of tumors ( Shikata et al, 2013 ; Singh et al, 2021 ), cardiovascular and cerebrovascular diseases ( Kozakova et al, 2019 ; Eckel et al, 2021 ), and other infections ( D'Elia et al, 1991 ; Knapp, 2013 ; Fang et al, 2021 ). NLRP3 inflammasome regulation by lncRNAs is a current research hotspot and has been widely documented in many diseases, such as inflammatory bowel diseases ( Samoilă et al, 2020 ), Parkinson’s disease ( Haque et al, 2020 ; Cao et al, 2021 ), and cancer ( Farooqi et al, 2020 ; Tang et al, 2020 ).…”
Section: The Mechanism Of Lncrna Involved In Nlrp3 Inflammasome Regulationmentioning
confidence: 99%
“…Several studies have shown that AMPK/mTOR signaling pathway is closely related to cell proliferation and is an important pathway in cancer development and progression [20][21][22][23][24] .Previously, our group has demonstrated that biguanide derivatives can exert anti-proliferative effects through AMPK/mTOR pathway [10] . Thus, Western Blotting was performed to evaluate the effect of the best active representa-tive compound 2B on AMPK/mTOR signaling pathway in T24, one of the representative cell lines.…”
Section: Chemistryselectmentioning
confidence: 99%